Cat Dreams - Le Guin, Ursula K. 1929-; Schindler, S. D. (New York : Orchard Books, 2009)
Presents a feline dreamland where it rains mice, all the dogs have run away, and a big bowl of kibbles and cream is waiting.
Keywords: Cats -- Fiction; Dreams -- Fiction; Stories in rhyme